The rights of the state auditor and guarantees of the exercise of his work : A comparative study - Rayan Aljarjari; Qabas Albadrani (الرافدین للحقوق, 2025)
The rights and legal guarantees granted to government accounting auditors are essential for ensuring their protection and empowerment while performing their duties. Providing auditors with rights and privileges enhances their ability to safeguard public funds effectively. Iraqi lawmakers, along with legislators in other comparative legal systems, have established rights that facilitate the auditor’s role, such as access to information and the ability to request data and clarifications. Despite variations among the legal frameworks of different countries, a common principle is maintaining proportionality in imposing disciplinary sanctions when auditors violate laws, regulations, or professional ethics. This study examines the legal framework for auditor protection and its effectiveness in combating financial corruption, a significant challenge facing the Iraqi state.